Morphological characterization of hemocytes in Ectemnaspis rorotaense (Floch & Abonnenc) and Ectemnaspis trombetense (Hamada, Py-Daniel & Adler) (Diptera: Simuliidae) - Silva, Juciane Conceição da; Pessoa, Felipe Arley Costa; Ríos-Velásquez, Cláudia Maria; Araújo, Helena Rocha Côrrea de; Feitosa, Ana Paula Sampaio; Alves, Luiz Carlos; Brayner, Fábio Andre; Medeiros, Jansen Fernandes (EntomoBrasilis, 2015)
Abstract. Hemocytes are insect immune cells which are responsible for processes of phagocytosis, encapsulation, and coagulation. This study aim to characterize the hemocyte cells in two species amazon blackflies: Ectemnaspis rorotaense (Floch & Abonnenc) and Ectemnaspis trombetense (Hamada, Py-Daniel & Adler). Black fly larvae and pupae were collected from streams in Presidente Figueiredo Municipality, Amazonas State, Brazil. Hemolymph of 36 individuals of E. rorotaense (12 larvae, 12 pupae and 12 adults) and 38 of E. trombetense (12 larvae, 12 pupae and 14 adults) were collected and the cells were characterized by light microscopy; 200 adults of each species were used to transmission electron microscopy study. In this work were showed, by the first time, the hemocyte cells of black flies amazon. Four cell types were identified: prohemocytes, granulocytes, oenocytoids, and plasmatocytes. Prohemocytes were the smallest cells and they exhibited a high nuclear-cytoplasmic ratio. Granulocytes possessed large, eccentric nuclei, and they were characterized by the presence of granules that differed in size and shape. Oenocytoids presented poorly developed nucleus with localization in central region. Plasmatocytes showed more morphological variations and large projections in the cytoplasmic membrane. The prohemocytes were the most frequent in E. rorotaense, with nearby 45% of total cells, whereas plasmatocytes and granulocytes, each one with 38%, were the most abundant in E. trombetense. This study showed that prohemocytes, granulocytes, oenocytoids, and plasmatocytes were present in the hemolymph of E. rorotaense and E. trombetense during all stages. Caracterização Morfológica de Hemócitos em Ectemnaspis rorotaense (Floch & Abonnenc) e Ectemnaspis trombetense (Hamada, Py-Daniel & Adler) (Diptera: Simuliidae) Resumo. Os hemócitos são células do sistema imune dos insetos responsáveis pelos processos de fagocitose, encapsulação e coagulação. O objetivo desse trabalho foi caracterizar os hemócitos nos simulídeos amazônicos, Ectemnaspis rorotaense (Floch & Abonnenc)e Ectemnaspis trombetense (Hamada, Py-Daniel & Adler). Larvas e pupas de simulídeos foram coletadas em igarapés no município de Presidente Figueiredo, Amazonas, Brasil. Para caracterização celular através da microscopia óptica, foi coletada a hemolinfa de 36 espécimes (12 larvas, 12 pupas e 12 adultos) de E. rorotaense e 38 espécimes (12 larvas, 12 pupas e 14 adultos) de E. trombetense. Para o estudo com microscopia eletrônica de transmissão, 200 adultos de cada espécie foram utilizados. Neste trabalho foram descritos, pela primeira vez, os hemócitos de simulídeos amazônicos. Foram identificados quatro tipos celulares em larvas, pupas e adultos: prohemócitos, plasmatócitos, granulócitos e oenocitóides. Os prohemócitos, com um núcleo volumoso em relação ao citoplasma, se mostraram as menores células. Os granulócitos foram caracterizados pela presença de grânulos de diferentes tamanhos e formas e um núcleo grande e excêntrico. Os oenocitóides revelaram núcleo pouco desenvolvido, geralmente localizado na região central. Os plasmatócitos apresentaram grandes projeções da membrana citoplasmática e maior variação morfológica. Os prohemócitos foram as células mais frequentes em E. rorotaense com 45% do total das células, enquanto os plasmatócitos e granulócitos, ambas com 38% cada, foram as mais abundantes em E. trombetense. Esse estudo mostrou que prohemócitos, granulócitos, oenocitóides e plasmatócitos são presentes na hemolinfa de E. rorotaense and E. trombetense durante todos os estágios.